The application of constitutively solvent‐tolerant P. taiwanensis VLB120ΔCΔttgV for stereospecific epoxidation of toxic styrene alleviates carrier solvent use. Issue 7 (4th May 2017) - Volmer, Jan; Schmid, Andreas; Bühler, Bruno
Abstract: For whole‐cell biotransformations involving toxic organic compounds, two‐liquid phase setups are typically applied employing an apolar extractive phase. Bis(2‐ethylhexyl)phthalate (BEHP) has proven to be an ideal solvent for stereospecific styrene epoxidation with recombinant E. coli, providing excellent extractive properties and a high biocompatibility. In eco‐efficiency evaluations, BEHP, however, has been identified as a critical factor regarding costs and environmental impact. In this study, the constitutive solvent tolerance of Pseudomonas taiwanensis VLB120Δ C Δ ttgV is shown to enable high specific activities (up to 180 U gCDW −1 ) and extensive reduction of the BEHP amount in two‐liquid phase setups and thus to constitute an excellent tool to improve the environmental and economic efficiency of such processes. At a 90% reduction of carrier solvent use and accordingly increased aqueous styrene concentrations, this strain still showed reasonably high specific styrene epoxidation activities (100 U gCDW −1 ), while the solvent‐adaptable wildtype strain immediately was toxified. A moderate 55% reduction of BEHP enabled a specific activity of 150 U gCDW −1 and thus represents a good trade‐off between volumetric productivity maximization and environmental impact minimization. These results for the first time show a clear benefit of a solvent‐tolerant compared to solvent‐sensitive host strains and how such a benefit can be achieved. Abstract : For whole‐cell biotransformations involving toxic organic compounds, two‐liquid phase setups are typically applied employing an apolar extractive carrier solvent. Such solvent use can constitute a critical factor regarding costs and environmental impact. In this study, a constitutively solvent‐tolerant Pseudomonas strain was shown to enable high specific activities as well as extensive reduction of solvent use and thus to constitute an excellent tool to improve the environmental and economic efficiency of such two‐liquid phase processes.